Impact of Price on Consumer Loyalty: The Mediating Role of Consumer Satisfaction at Extract Café Pekanbaru (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to determine the effect of price on customer loyalty through customer satisfaction as an intervening variable at Extract Café Pekanbaru.. Methodology: In this study, a purposive sampling technique was used to sample 100 respondents. The method used was descriptive statistics with a quantitative approach. Measurement models, structural models, and hypothesis testing with SmartPLS4 software analyze data with a Likert scale. Results: the results show that price has a positive and significant effect directly on consumer loyalty with a T-statistic of 2.969> 1.96 and a p-value of 0.003 1.96 and a p-value of 0.000 1.96 and a p-value of 0.000 1.96 and a p-value of 0.000